Environmental Monitoring - Wiersma, G. Bruce (CRC Press, 2009)
The current rate and scale of environmental change around the world makes the detection and understanding of these changes increasingly urgent. Subsequently, government legislation is focusing on measurable results of environmental programs, requiring researchers to employ effective and efficient methods for acquiring high-quality data.